The new US strategy towards Asia : adapting to the American pivot - Tow, William T.; Stuart, Douglas T. (London : Routledge, 2015)
'Barack Obama's'rebalancing strategy' or'pivot strategy', intended to demonstrate continued US commitment to the Asia Pacific region in a variety of military, economic and diplomatic contexts, was launched with much fanfare in 2011. Implicit in the new strategy is a focus on China and also a US relience on existing regional allies to implement its strategy. This book explores the impact of the new strategy on the US's allies in the region, and the allies' responses. Overall, the book outlines the deep complexities of the United States' exercise of power and influence in the region'--
part 1. Asia's place in America's global strategy -- part 2. Northeast Asian partners and allies -- part 3. Southeast Asian partners and allies -- part 4. The wider Indo-Pacific region.
Includes bibliographical references and index.
Mode of access: World Wide Web.
Keywords: United States -- Foreign relations -- Asia; Asia -- Foreign relations -- United States; United States -- Foreign relations -- 2009-